2009
DOI: 10.1007/s00408-009-9140-z
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Diaphragmatic Paralysis: Bell’s Palsy of the Diaphragm?

Abstract: The results of this small, preliminary study suggest that antiviral therapy with valacyclovir may be helpful in the treatment of idiopathic diaphragm paralysis induced by a viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
0
17
0
3
Order By: Relevance
“…Crausman et al reported three cases of subacute unilateral diaphragmatic paralysis with a history of subacute or acute onset of neck or shoulder pain (37). All three cases were empirically treated with antiviral therapy, which resulted in alleviation.…”
Section: Discussionmentioning
confidence: 99%
“…Crausman et al reported three cases of subacute unilateral diaphragmatic paralysis with a history of subacute or acute onset of neck or shoulder pain (37). All three cases were empirically treated with antiviral therapy, which resulted in alleviation.…”
Section: Discussionmentioning
confidence: 99%
“…In a significant number of cases, no cause is found. Diaphragmatic paralysis may be an early sign of systemic diseases, like systemic lupus erythematosus, metabolic diseases, motor neuron disease or thoracic malignancy [9]. Bilateral diaphragmatic paralysis is more common in systemic diseases such as myopathies or metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These authors consider isolated diaphragmatic paralysis as a "Bells palsy" of the phrenic nerve (Crausman et al, 2009). …”
Section: Acute Diaphragmatic Paralysismentioning
confidence: 99%